Secnidazole for control of giardiasis in dairy calves - Volpato A.* (2018)
© 2018 Elsevier Inc.The aim of this study was to verify whether secnidazole, given in a single oral dose (10 mg/kg), decreases or eliminates the excretion of Giardia duodenalis cysts. Holstein calves were raised from birth to 15 ± 2 days of age in individual stalls. Subsequently, 12 calves were grouped and housed in collective stalls. After seven days (day of life 21), we collected stool samples directly from the rectal ampulla in order to determine the degree of parasitic infection. Fecal examination was performed by a centrifugal-flotation technique, which allows for visualization and quantification of G. duodenalis cysts. After division into control and treatment groups, six animals were treated with one 400 mg secnidazole capsule. The first stool collection following treatment was performed on day 5 and the second on day 30. This experiment was repeated at 15 days, with a total of 24 calves studied. Animals on the farm where the experiment was conducted often suffer from giardiasis, despite hygiene care (disinfection) and adequate facilities. All 24 calves were excreting G. duodenalis cysts prior to starting treatment. Five days after receiving the treatment, animals in the experiment group were Giardia-negative, i.e., they did not excrete parasite cysts, whereas calves in the control group continued to excrete cysts. After 30 days of treatment, the stool of most treated animals (83.3%) remained free of G. duodenalis cysts. Therefore, we believe that secnidazole was 100% effective in eliminating the excretion of Giardia duodenalis cysts.